Meal replacements and fibre supplement as a strategy for weight loss. Proprietary PGX® meal replacement and PGX® fibre supplement in addition to a calorie-restricted diet to achieve weight loss in a clinical setting - Reichert, R.; Reimer, R.; Kacinik, V.; Pal, Sebely; Gahler, R.; Wood, S. (Taylor & Francis, 2013)
Meal replacements and viscous soluble fibre represent safe and sustainable aids for weight loss. Our purpose was to determine if PGX® meal replacements and PGX® fibre complex in combination with a calorie-restricted diet would aid in weight loss in a clinical setting. Fifty-two overweight and obese participants (49 women, 3 men; average age 47.1 years) with a mean body mass index (BMI) of 33.8 ± 6.4 kg/m2 consumed 57 g of proprietary PGX® meal replacement product at breakfast and another 57 g at lunch for 12 weeks. In addition to the meal replacements, they were also asked to consume 5 g/day of PGX® fibre in the form of granules, powder or capsules together with 250 mlwater. A registered dietician recommended low-fat, low-glycaemic-index foods for snacks and the dinner menus such that each volunteer was consuming a total of 1200 kcal/day. All participants (n = 52) lost a significant amount of weight from baseline (−4.69 ± 3.73 kg), which was further reflected in the reductions in their waist (−7.11 ± 6.35 cm) and hip circumference (−5.59 ± 3.58 cm) over the 12-week study (p < 0.0001). BMI scores (n = 51) were reduced by 1.6 ± 1.4 kg/m2. The use of PGX® meal replacements and PGX® fibre along with a controlled dietary caloric intake is of benefit for short-term weight loss.